2009
DOI: 10.1007/s11064-009-9997-5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Oxidative Stress Associated with the Neurological Diseases of Aging

Abstract: Markers of oxidative stress were measured in blood samples of 338 subjects (965 observations): Alzheimer's, vascular dementia, diabetes (type II) superimposed to dementias, Parkinson's disease and controls. Patients showed increased thiobarbituric acid reactive substances (+21%; P < 0.05), copper-zinc superoxide dismutase (+64%; P < 0.001) and decreased antioxidant capacity (-28%; P < 0.001); pairs of variables resulted linearly related across groups (P < 0.001). Catalase and glutathione peroxidase, involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 56 publications
2
36
2
4
Order By: Relevance
“…Moreover, the present results show linearity between pairs of oxidative stress variables and the ordering of the neurological patients' diseases along the different regression lines pointing to the existence of an overall balance between oxidative insult, damage and protection (Table 2 and Figures 8 and 9) (Serra et al, 2009). The linear correlations described between the three variables also include a significant negative linear correlation between plasma TRAP and erythrocyte SOD (r = -0.980, p < 0.001, not shown), which is implied by the other two relationships.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Moreover, the present results show linearity between pairs of oxidative stress variables and the ordering of the neurological patients' diseases along the different regression lines pointing to the existence of an overall balance between oxidative insult, damage and protection (Table 2 and Figures 8 and 9) (Serra et al, 2009). The linear correlations described between the three variables also include a significant negative linear correlation between plasma TRAP and erythrocyte SOD (r = -0.980, p < 0.001, not shown), which is implied by the other two relationships.…”
Section: Resultssupporting
confidence: 60%
“…These three increases are indicative of the occurrence of systemic oxidative stress. Present results demonstrate that the BOOH-CL, TBARS, TRAP and SOD variables for determining oxidative stress and antioxidant status would be a useful tool for the biochemical and clinical evaluation of patients during the progression of the disease and clinical treatment (Repetto, 2008;Serra et al, 2009). Chemiluminescence methods allow evaluating and quantifying the toxic oxygen species and antioxidant defenses in blood samples of the patients.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The increase of tert-butyl hydroperoxide-initiated chemiluminescence is indicative that -tocopherol is the antioxidant consumed in erythrocytes and suggest that reactive oxygen species and lipid peroxidation catalyzed by reduced transition metals may be responsible for the onset of oxidative damage and the occurrence of systemic oxidative stress in patients suffering oxidative damage associated to neurological pathologies as Parkinson (Famulari et al, 1996, Dominguez et al, 2008, Alzheimer disease (Famulari et al, 1996;Repetto et al, 1999;Dominguez et al, 2008;Serra et al, 2009), and vascular dementia (Famulari et al, 1996, Dominguez et al, 2008Serra et al, 2009); immunological diseases as HIV infection and AIDS , hyperthyroidism and hypothyroidism (Abalovich et al, 2003). These methods were used to evaluate lipid peroxidation and oxidative damage in experimental models of oxidative stress in rats Ossani et al, 2007;Repetto  Ossani, 2008;.…”
Section: ¹O2mentioning
confidence: 99%
“…The intensive production of ROS are widely seen in PD (Nikam et al 2009;Reddy and Reddy 2011;Chakrabarti et al 2011;Jomova et al 2010), as indicated by an increase in the contents of lipid peroxidation in blood samples of patients with PD (Serra et al 2009). Copper ions are very likely involved in this process (Greenough et al 2013).…”
Section: Coppermentioning
confidence: 99%